A determination of challenges and opportunities faced by small, medium micro entreprises (SMMES) in Fetakgomo Local Municipality, Sekhukhune in Limpopo Province - Debeila, Ozymancious Seripele (My University, 2018)
In a country with a high unemployment rate, such as South Africa, the role played by small, medium and micro enterprises (SMMEs) cannot be undermined in creating jobs. SMMEs are crucial in the labour market, as they aim to curb and stimulate economic growth and development in South Africa. The aim of this study is to revisit or establish challenges and opportunities for the growth of SMMEs. The study was based on data collected from SMME entrepreneurs in the Sekhukhune area of Fetakgomo Municipality in Limpopo Province. The population of this study consisted of 53 respondents. The researcher had previously administered the instruments to a pilot group to examine the user-friendliness, comprehensiveness and adequacy of the data collection procedures and instruments. In addition, the data were analysed to establish the adequacy of the data analysis plan of actionSampling refers to the procedure by which a given number of subjects from a population are selected to represent that population. According to Babbie et al. (2001:104), a sample representative of a population or universe is taken from any portion of that population or universe. In terms of sample size consideration, according to Maree (2007), larger samples are better in terms of representativeness, statistical analysis and accuracy. In the present study, 53 people were interviewed to thoroughly determine the challenges and opportunities of SMMEs in the area. Snowball and convenience sampling methods were utilised to interview the SMMEs.The data were analysed using descriptive statistics. The results indicate that to improve the growth of SMMEs, the government should actively hold campaigns to enlighten the public of their supportive service structures that they offer to encourage emerging SMMEs to partake in various local business chambers to access business support. Internally, the entrepreneurs and their staff should engage in business training to enhance their entrepreneurial skills. The study recommends that the government needs to realign the current policy on SMMEs to encompass the dynamic economic changes in supporting the role made by this sector in the business environment with a view to improve their growth. The study established the need for an increased awareness to emerging SMMEs on opportunities available to them to develop and grow their businesses. Furthermore, this development and growth can be improved by creating incentives for financiers to extend their credit and loan offers to SMMEs, coupled with tax incentives for that comply.
Thesis (MBA.) --University of Limpopo, 2018
Keywords: SMMEs; Small business; Challenges; Opportunities; Business enterprises; Small business